Development and optimization of a novel PLGA-Levan based drug delivery system for curcumin, using a quality-by-design approach - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (ELSEVIER, 2019)
This study aimed to develop a PLGA, Levan-based drug delivery system (DDS) of Curcumin using a quality-by-design (QbD) approach to reveal how formulation parameters affect the critical quality attributes (CQAs) of this DDS and to present an optimal design. First, a risk assessment was conducted to determine the impact of various process parameters on the CQAs of the DDS (i.e., average particle size, ZP, encapsulation efficiency and polydispersity index). Plackett-Burman design revealed that potential risk factors were Levan molecular weight, PLGA amount and acetone amount. Then, the optimization of the DDS was achieved through a Box-Behnken Design. The optimum formulation was prepared using low molecular weight Levan (134 kDa), 51.51 mg PLGA and 10 ml acetone. The model was validated and the optimized formulation was further characterized using different physic-chemical methods. The study resulted in the most stable NP with a spherical and uniform shape and physical stability tests indicated its stability for at least 60 days at room temperature. In conclusion, this study was an effort for developing a DDS which solubilizes Curcumin in clinically applicable concentrations.
Keywords: Curcumin; Levan; PLGA; Quality by design; Nano drug delivery; Plackett-Burman; Box-Behnken; SOLID LIPID NANOPARTICLES; HALOMONAS-SMYRNENSIS; FORMULATION; BIOAVAILABILITY; VARIABLES; BLEND; MODEL; SIZE